2010
DOI: 10.1016/j.tsf.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Carbide and nanocomposite thin films in the Ti–Pt–C system

Abstract: Thin films in the Ti-Pt-C system were deposited by non-reactive, DC-magnetron sputtering.Samples were characterised using X-ray photoelectron spectroscopy, X-ray diffraction, and transmission electron microscopy. A previously not reported metastable solid solution carbide, (Ti 1-x Pt x )C y with a Pt/Ti ratio of up to 0.43 was observed. This solid solution phase was present both as single phase in polycrystalline samples, and together with amorphous carbon (a-C) in nanocomposite samples. Annealing of nanocompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…This effect was more pronounced in the coatings with low amount of carbon and high amount of nickel. A similar phenomenon of grain size decrease initiated by third-element doping was observed in other carbide systems [21,37,43,44]. Råsander et.…”
Section: Discussionsupporting
confidence: 75%
“…This effect was more pronounced in the coatings with low amount of carbon and high amount of nickel. A similar phenomenon of grain size decrease initiated by third-element doping was observed in other carbide systems [21,37,43,44]. Råsander et.…”
Section: Discussionsupporting
confidence: 75%
“…We did not observe a positive shift in Pt 4f or a negative shift in C 1s expected for Pt carbides, which would result from the charge transfer from Pt to C if Pt carbides would form during heat-treatment as suggested by previous studies. 35,36 Further analysis was carried out after calibrating with the sp 2 hybridized C 1s at 284.5 eV. Pt 4f 5/2 and 4f 7/2 profiles of these five Pt/C samples were fitted to three components: Pt 0 , Pt (II) and Pt (IV) species with peak separation and peak ratio constrained, as shown in Figure S3 and Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Fe, Ni, Pt and Al, can be dissolved into TiC to form ternary TMC systems. [2][3][4][5][6][7][8] Furthermore, we find that the presence of TM impurities greatly affects the stability and mobility of C atoms in the vicinity of the TM. Especially, the C vacancy formation energy is always lower in the presence of the impurities compared to pure TiC, and therefore the impurities will attract C vacancies.…”
Section: Discussionmentioning
confidence: 85%
“…[3][4][5] In experiments on thin films of nanocrystalline (Ti,M)C, where the carbide phase is embedded in an amorphous C matrix, i.e. (nc-(Ti,M)C/a-C), it has been shown that the alloying with weak carbide forming metals, M, yields a larger amount of C matrix in relation to the carbide phase for systems with identical carbon-to-metal ratio during growth compared to systems that only contain Ti and C. [2][3][4][5][6][7][8] Furthermore, it has been shown that during heat treatment at elevated temperatures there is also an increase of the C matrix phase for the alloyed samples which is not present in the binary systems. [3][4][5] When used as a surface coating material, the ternary solutions yield a lower friction coefficient than the binary samples while maintaining a relatively high degree of hardness.…”
Section: Introductionmentioning
confidence: 99%